The Psychological Contract: The Changing Nature of Employee-Employer Expectations - Bala, Ms. Indu (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
The psychological contract describes a phenomenon that occurs largely in the minds of employers and employees . The term governs all the ideas and expectations that workers have about their jobs and includes beliefs about their roles and responsibilities as employees. One of the fundamental challenges for HR is to help management maintain the appropriate balance between the realities of the business model and the needs of our employees. Success comes when the balance exists and is understood ( Kevin Sullivan Former VP of HR).There is a great challenge for a business today- a basic shift in employment expectations both from the employee’s and the company perspectives. Both the right person and the right job are being affected by changing values. This research paper tries to find out the expectations of employers and employees in the present era . A detailed overview of any organization has been undertaken. Various ways have been suggested to deal with situation and emotions when expectations are not being met.